A double core–shell modification of bulk TiO2 microspheres into porous N-doped-graphene carbon nanoflakes/N-doped TiO2 microspheres for lithium-ion battery anodes1. Issue 48 (28th May 2015) - Rajagopalan, Balasubramaniyan; Oh, Eun-Suok; Choi, Won Mook; Chung, Jin Suk
<x xml:space="preserve">Abstract</x> Nitrogen (N) doping and double core–shell modification of TiO2 for lithium battery application.